2017
DOI: 10.1523/jneurosci.0936-17.2017
|View full text |Cite
|
Sign up to set email alerts
|

Abnormal Microglia and Enhanced Inflammation-Related Gene Transcription in Mice with Conditional Deletion ofCtcfinCamk2a-Cre-Expressing Neurons

Abstract: CCCTC-binding factor (CTCF) is an 11 zinc finger DNA-binding domain protein that regulates gene expression by modifying 3D chromatin structure. Human mutations in cause intellectual disability and autistic features. Knocking out in mouse embryonic neurons is lethal by neonatal age, but the effects of CTCF deficiency in postnatal neurons are less well studied. We knocked out postnatally in glutamatergic forebrain neurons under the control of ; ( CKO) mice of both sexes were viable and exhibited profound deficit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
53
1

Year Published

2018
2018
2024
2024

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 60 publications
(58 citation statements)
references
References 97 publications
4
53
1
Order By: Relevance
“…e IgG levels in ipsilesional brain tissues from DEREG and WT mice were not significantly (ns) different (Fig. 4e, p = 0.063, oneway ANOVA followed by Tukey's multiple comparison test) expression of inflammation-related genes either in response to environmental factors [65] or to genetic factors [66]. Along with the observation of increased IFN-γ expression, our results from the rotarod performance test indicate that the depletion of Tregs causes transient aggravation of motor deficits at 1 dpi.…”
Section: Discussionmentioning
confidence: 94%
“…e IgG levels in ipsilesional brain tissues from DEREG and WT mice were not significantly (ns) different (Fig. 4e, p = 0.063, oneway ANOVA followed by Tukey's multiple comparison test) expression of inflammation-related genes either in response to environmental factors [65] or to genetic factors [66]. Along with the observation of increased IFN-γ expression, our results from the rotarod performance test indicate that the depletion of Tregs causes transient aggravation of motor deficits at 1 dpi.…”
Section: Discussionmentioning
confidence: 94%
“…Intriguingly, both chemokines were also found to be elevated in patients with autism spectrum disorders (AL-Ayadhi & Mostafa, 2013). In line, during the revision of this article, a study was published showing that conditional ablation of the CCCTC-binding factor (CTCF) in Camk2a-expressing neurons led to increased expression of Ccl17 in hippocampal neurons, accompanied by elevated proportions and altered morphology of microglia in the hippocampus, and behavioral deficiencies of the mice in spatial learning and memory (McGill et al, 2018). Furthermore, a recent study by Shen et al reported that repeated LPS stimulation in postnatal mice caused a higher susceptibility to epileptic seizures depending on TLR4 expression and MyD88 signaling in astrocytes, whereas LPS stimulation in later life mainly activated microglia but did not increase the incidence of epileptic seizures (Shen et al, 2016).…”
Section: Ccl17 Affects Synaptic Transmission In the Ca1 Regionmentioning
confidence: 90%
“…For example, multiple studies in mouse Mecp2 mutant models of Rett syndrome show evidence of microglial activation and involvement in disease progression (Derecki et al 2012;Cronk et al 2015;Horiuchi et al 2016). In addition, conditional deletion of CCCTC binding factor (CTCF) specifically in postnatal glutamatergic forebrain neurons in mice decreased neuronal dendritic spine density, and microglia in these animals adopt an abnormal morphology and up-regulate transcription of microglial inflammatory genes (Mcgill et al 2017). Therefore, immune signatures observed across transcriptomic and epigenomic studies in human ASD brain may be partially driven by an immune response to abnormal neuronal processes that arise from genetic and epigenetic etiologies.…”
Section: Discussionmentioning
confidence: 99%